SOFTWARE TOOLS FOR MODELING of physical processes in the protection of the speech information - I. V. Savchenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A version of software for the simulation of physical processes in the protection of the speech information in the Java language in the software package Eclipse is shown. The simulated system consists of a set of classes and patterns generalizing common approaches to solving problems of acoustic beam method.The model demonstrates the process of propagation of sound waves in a room with a view of multiple reflections from obstacles.